2017
DOI: 10.1038/s41598-017-07189-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated diagnostic network construction reveals a 4-gene panel and 5 cancer hallmarks driving breast cancer heterogeneity

Abstract: Breast cancer encompasses a group of heterogeneous diseases, each associated with distinct clinical implications. Dozens of molecular biomarkers capable of categorizing tumors into clinically relevant subgroups have been proposed which, though considerably contribute in precision medicine, complicate our understandings toward breast cancer subtyping and its clinical translation. To decipher the networking of markers with diagnostic roles on breast carcinomas, we constructed the diagnostic networks by incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 85 publications
0
29
2
Order By: Relevance
“…carcinoma [11,12,27,30,34]. On the contrary, in this study, we noted that overexpression of [11,12].…”
Section: Downregulation Of Fam134b Is Associated With Adverse Clinicocontrasting
confidence: 73%
See 1 more Smart Citation
“…carcinoma [11,12,27,30,34]. On the contrary, in this study, we noted that overexpression of [11,12].…”
Section: Downregulation Of Fam134b Is Associated With Adverse Clinicocontrasting
confidence: 73%
“…Initial studies revealed that FAM134B acts as a transforming gene in ESCC and is overexpressed in ESCC cells [9]. Subsequent studies noted that FAM134B acts as a tumor suppressor and inhibits cancer growth in colorectal adenocarcinoma and breast carcinoma [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…ALCAM‐negative was described in 22% in a series with 2197 unselected BC patients, and similar rates were confirmed in smaller series. Based on the function of ALCAM as a cell adhesion molecule, it appears possible that loss of such a protein would result in more adverse cancer cell behavior due to a facilitated tissue infiltration for developing metastases and different series described its association with higher rates of recurrences, shorter survival, advanced stages, unfavorable tumor grade, and high Ki67 . However, we did not find the association between membrane ALCAM expression and survival in our series, nor its association with higher stage or higher Ki67.…”
contrasting
confidence: 81%
“…Its expression in breast cancer (BC) is associated with aggressive clinicopathological features. Dai et al found that ALCAM is a negative prognosis marker, and its combination with other three genes related to cancer hallmarks is equivalent to previously identified 1015 genes for BC subtyping and has a remarkable role in distinguishing TNBC subtype …”
mentioning
confidence: 80%
See 1 more Smart Citation